EXPERT SYSTEM FOR DEVELOPMENT DIAGNOSING DISEASE WITH HEPATITIS USING WAMP - Nia Septiyani; Sahni Damerianta (Jurnal Sistem Informasi, 2008)
Abstract :Expert systems are computer-based system that usesknowledge, facts and reasoning techniques in solving problemsusually only be solved by an expert in a particular field. Systemexperts to provide added value in technology to assist in handlingera of increasingly sophisticated information.Expert System produces output in the form of disease possiblehepatitis based on symptoms suffered by the user. This system alsomanampilkan amount of trust against the possibility of disease symptomskidney suffered by the user. The value of these beliefs isresults of calculations using the method-Factor Certainly.This expert system is designed with the view that considering the ease inin pengoprasiannya.Bibliography : (xiv + 93 + 33 Appendix)